Studies of Failure of High–Strength Concrete - Hoła, J. (Engineering Transactions, 1998)
This paper presents results of studies, conducted by means of the acoustic emission technique and strain measurements, of the failure of high-quality concrete. Several concretes differing in their composition and compression strength were tested. It has been determined that the failure of high-strength concrete can be regarded as a three-stage process. The values of the stresses initiating the stable development of microcracks and those of the critical stresses after which the unstable development and propagation of microcracks begin were determined. It has been established that the values of these stresses for the tested concretes depend on compression strength and they increase with this strength. The obtained results are of significance to both the theory and practice.